Two Cases of Microperforation of the Transverse Vaginal Septum - Sangeeta Rai,; Royana Singh, (Faculty of Medicine, UKM Medical Centre, 2015)
Primary amenorrhoea with microperforate transverse vaginal septum is a rare entity with varied incidence in different parts of the world. It may be asymptomatic, unlike imperforate hymen. Depending on the size of the microperforation in transverse vaginal septum clinical features may vary similar to those found in imperforate hymen cases. We report two cases of a 25 and 22-year-old women who sought the gynaecologist with complains of primary infertility. They had normal menses with one of them having secondary dysmenorrhea. Physical examination and imaging disclosed microperforation of transverse vaginal septum in the upper part of the vagina at mid point position. Resection of the septum under anesthesia was done. The outcome was favourable and 25 year asymptomatic patient with primary infertility at the present moment have conceived carrying six weeks pregnancy and second patient is in follow up. We conclude that this anomaly may be overlooked, interfering on its incidence determination. The finding of transverse vaginal septum in an asymptomatic infertility patient is highly unusual. Clinicians must be aware of atypical presentations and potential multifactorial etiologies of primary infertility. Ensuring a thorough evaluation is essential in order to mitigate long-term effects of a misdiagnosis.